Using A Constructivist Approach to Improve Students’ Comprehension in Reading Descriptive Text at The Seventh Grade of SMP Negeri 24 Pekanbaru - Santika, Reka; Herdi, Herdi (Elsya : Journal of English Language Studies, 2020)
The problem of this research is the students’ low comprehension in reading descriptive text in term of generic structure, purpose, language features and vocabulary. This research aimed to enhance student understanding by using a constructivist approach in reading descriptive text. The design of this research was a classroom action research (CAR). The samples of this research were 40 students. Based on the result of the test, it was found that students’ average score was 77. The resulting score improved from the based score that was 69.5. Furthermore from the result of observation, field note and interview, it was found the factors influencing the improvement of students’ comprehension in reading descriptive text by using a constructivist approach, they were teacher’s strategy and teacher’s media. Finally, the researcher concludes that this constructivist approach can improve the students’ reading comprehension.